A look at the vestiges of historiography of philosophy in official documents and in the tradition of philosophy teacher's education - Rodrigues, Augusto [UNESP]; Gelamo, Rodrigo Pelloso [UNESP] (Univ Federal Santa Maria, 2020)
The aim of this article is to point to the vestiges of an educational heritage that provides guidelines for the subject of Philosophy in basic education and also models Philosophy teachers' education. This reconstruction is initially grounded on two official documents that are basic to the construction of Sao Paulo State Curriculum - Parametros Curriculares Nacionais and Orientacoes Curriculares para o Ensino Medio - and on the texts by Leopoldo e Silva. From the reading of these writings, there will be fundamental elements that allow associating the theoretical-philosophical guidelines to the educational tradition in Philosophy consolidated in the undergraduate course of Philosophy of University of Sao Paulo. In order to show their resonances in the practices of teaching and learning Philosophy, the methodological apparatuses responsible for the construction of a technical-academic standard are rescued. These can be partially evidenced in Jean Maugue's texts and, fundamentally, in the philosophical practices of Martial Gueroult and Victor Goldschmidt. Finally, as long as the origin of these practices is reconstructed with Philosophy, their own possibilities to think the present are strained.
Keywords: Philosophy teaching in basic education; Philosophy teacher's education; historiography of Philosophy